Elaborating a master model of leadership: A paper on the fundamental leadership qualifications in the workplace - Cotrim, J. (2nd International OFEL Conference on Governance, Management and Entrepreneurship, Abstracts of the proceedings, 2014)
Leadership is an enthralling theme to many investigators and professionals from all sectors of activity. It has been considered a key topic in labour relations, as many consider that the applied style of leadership may be a trigger factor for labour conflicts. Further, the theme has also generated much discussion around personal and/or professional incompatibilities between the leader and his/her followers, the co-existence of formal and informal leaderships, as well as, the integration of different styles of leading along the hierarchy chain within an organization. One may find an extensive range of contributions and theories on the theme from many investigators, authors and professionals. Each of them presents their own view on how one should perceive leadership. Many views coincide with each other, while others look at the topic from different angles and suggest alternatives ways of conceiving leadership. For the purposes of this paper, one may clearly identify two main trends of thinking regarding leadership: one that traditionally perceives leadership as depending on the personal and innate characteristics of the individual, and a second one that conceives leadership as largely depending on the social learning from the individual – also known as the process of leadership approach. Without neglecting the mentioned traditional approach to leadership, this paper represents an attempt to explore new ways of looking at leadership and, more specifically, deepen the discussion around the pertinence of the process of leadership approach, where one may clearly identify some crucial elements and factors that play a decisive role in the quality of the leadership applied by a leader. The discussion on this in contrast to the analysis made to one case study – Wipro BPO enterprise – will, ultimately, lead to one result: the proposal of a new model of leadership.